Risk of bias and reporting practices in studies comparing VO2max responses to sprint interval vs. continuous training: A systematic review and meta-analysis - Bonafiglia, J. T.; Islam, H.; Preobrazenski, N.; Gurd, B. J. (Journal of Sport and Health Science, 2022)
Background It remains unclear whether studies comparing maximal oxygen uptake (VO2max) response to sprint interval training (SIT) vs. moderate-intensity continuous training (MICT) are associated with a high risk of bias and poor reporting quality. The purpose of this study was to evaluate the risk of bias and quality of reporting in studies comparing changes in VO2max between SIT and MICT.